Dermoscopy Supports the Diagnose of Papulosquamous Disorders - Alinda, Medhi Denisa; Hutomo, Marsudi; Setyaningrum, Trisniartami (Faculty Of Medicine Airlangga University, 2014)
Background: The diagnose of papulosquamous skin disorder was established by clinical symptoms. However, some of papulosquamous manifestation are alike with each other and lead to misdiagnostic. Histopathology examination usually can help to establish diagnose but this method is invasive and time consuming. Purpose: To evaluate dermoscopic features of papulosquamous disorder. Methods: Descriptive observasional cross sectional study, total sampling in ward and out patient clinic of Dermato-venereology Department Dr. Soetomo General Hospital. Twenty four samples were included in the study, followed by the procedures from anamnesis, physical examination, dermoscopy procedures, and histopathology examination. Results: From 24 samples, 19 samples showed plaque psoriasis describing 12 ring patterns, 1 cluster pattern, 2 patchy patterns, 2 reguler patterns, and 2 unspesiï¬c patterns; 3 samples showed nummular dermatitis describing 2 cluster patterns and 1 unspesiï¬c pattern; and 2 samples showed pityriasis rosea describing 2 pheripery patterns. Conclusion: Dermoscopy can support the diagnosis of papulosquamous skin disorder especially plaque psoriasis.Key words: papulosquamous disorder, dermosocopy, histopathology examination, plaque psoriasis.